Facultative Apomixis in Garcinia atroviridis (Clusiaceae) and Effects of Different Pollination Regimes on Reproductive Success - Sasithorn Pangsuban; Noparat Bamroongrugsa; Kamnoon Kanchanapoom; Charassri Nualsri (Tropical Life Sciences Research, 2009)
Various aspects of the reproductive success of Garcinia atroviridis Griff. were studied. Controlled pollination experiments were carried out in an orchard located in Songkhla province, southern Thailand, from February to July 2003. Floral longevity, stigma receptivity, and pollen viability were examined before carrying out the experiments. Three pollination treatments were compared: open pollination, manual pollination with bags, and bags without pollination (apogamy). Although there was no significant difference in the initial fruit set, bagged and manual pollination produced a significantly greater fruit drop rate than apogamy or natural pollination at one week after the flowers had been pollinated. On the other hand, the apogamy treatment had a greater fruit drop rate than natural and manual pollination treatments before fruit maturation. In addition, unpollinated bagged flowers bore fewer and smaller fruit than naturally and manually cross-pollinated flowers. Although the fruits from unpollinated flowers were capable of asexual seed formation, they produced fewer seeds and had poorer seed quality (defined as average fresh weight and germination rate) than those from the other treatments. The occurrence of asexual and sexual reproduction was also studied using Random Amplification of Polymorphic DNA (RAPD) analysis and by comparing the patterns of bands produced from DNA extracted from the offspring of the naturally cross-pollinated fruits. On average, 58% of the offspring had a genetic constitution identical to that of the maternal parent (ranging from 36% to 87%), indicating that some offspring were produced without prior fertilisation. However, the remainder showed polymorphism, demonstrating the occurrence of sexual reproduction. These findings indicate that facultative apomixis occurred in the study population. However, a residual sexuality was important for fruit production, fruit size, normal seed set and seed quality. Pelbagai aspek kejayaan dalam pembiakan Garcinia atroviridis Griff. telah dikaji. Eksperimen pendebungaan terkawal telah dijalankan di dalam sebuah kebun di wilayah Songkhla, selatan Thailand, dari Februari hingga Julai 2003. Kelanjutan usia bagi bunga, reseptiviti stigma dan keboleh hidupan debunga telah diperiksa sebelum eksperimen dijalankan. Tiada perbezaan yang signifikan dalam set buah awal antara tiga jenis rawatan pendebungaan, iaitu pendebungaan terbuka, pendebungaan dibeg dan manual, dan dibeg tanpa pendebungaan (apogami). Walau bagaimanapun, pendebungaan dibeg dan manual telah menghasilkan kadar jatuh buah yang jauh lebih signifikan daripada apogami dan pendebungaan semulajadi, yang dikesan satu minggu selepas bunga-bunga tersebut telah didebungakan. Rawatan apogami mempunyai kadar jatuh buah yang lebih besar berbanding pendebungaan semulajadi dan manual sebelum buah masak. Dalam pada itu, kebolehan membuah serta saiz buah didapati kurang dalam bunga-bunga yang dibeg tanpa pendebungaan, berbanding dengan bunga-bunga pendebungaan semulajadi dan pendebungaan silang. Walaupun buah daripada bunga-bunga yang tidak didebungakan boleh menjalani pembentukan benih secara aseksual, buah-buah ini menghasilkan nombor purata benih yang kurang, dan kualiti benih yang teruk dan kurang memuaskan (didefinasikan sebagai berat bersih purata dan kadar percambahan) berbanding dengan rawatan-rawatan yang lain. Pembiakan aseksual dan seksual juga dikaji menggunakan analisis Random Amplification of Polymorphic DNA (RAPD) dan melalui pembezaan corakcorak jalur yang dihasilkan daripada DNA yang diekstrak daripada baka buah yang melakukan pendebungaan silang secara semula jadi. Secara purata, 58% daripada baka tersebut mempunyai konstitusi genetik yang sama dengan induk (dari 36%–87%), yang menunjukkan ada di antara baka dihasilkan tanpa penyuburan. Penemuan ini mencadangkan bahawa apomisis fakultatif telah berlaku dalam populasi yang dikaji. Walaubagaimanapun, suatu residual seksual adalah penting untuk penghasilan buah, saiz buah, set biji benih normal dan kualiti benih.